Influential Article Review - Experimental Studies In Innovation Research - Daniel, Timothy; Keller, Jeannette (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines innovation. We present insights from a highly influential paper. Here are the highlights from this paper: Innovation research has developed a broad set of methodological approaches in recent decades. In this paper, we propose laboratory experiments as a fruitful methodological addition to the existing methods in innovation research. Therefore, we provide an overview of the existing methods, discuss the advantages and limitations of laboratory experiments, and review experimental studies dealing with different fields of innovation policy, namely intellectual property rights, financial instruments, payment schemes, and R&D competition. These studies show that laboratory experiments can fruitfully complement the established methods in innovation research and provide novel empirical evidence by creating and analyzing counterfactual situations. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.